2022
DOI: 10.2147/jir.s349818
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Microparticles Derived from Primary Pulmonary Microvascular Endothelial Cells Mediate Lung Inflammation in Chronic Obstructive Pulmonary Disease by Transferring microRNA-126

Abstract: Background: Extracellular vesicles (EVs) are considered to new types of intercellular communication media, and microRNA is one of the most common transferring components of EVs. This study aimed to explore the potential role of endothelial microparticles (EMPs) derived from primary pulmonary microvascular endothelial cells in regulating lung inflammation of chronic obstructive pulmonary disease (COPD) through transferring microRNA-126 (miR-126). Methods: EMPs generated from primary pulmonary microvascular endo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 61 publications
0
5
0
1
Order By: Relevance
“…Endothelial microparticles derived from endothelial cells can reduce the expression of HMGB1 in epithelial cells. This downregulated the release of TNF‐α and IL‐1β and then attenuated CSE‐induced inflammation in HBE cells 117 . The expression level of miR‐181a‐5p was lower in the lung tissues of COPD model mice.…”
Section: Inhibition or Blockade Of Hmgb1 Rage And Tlr4 As A Potential...mentioning
confidence: 88%
See 1 more Smart Citation
“…Endothelial microparticles derived from endothelial cells can reduce the expression of HMGB1 in epithelial cells. This downregulated the release of TNF‐α and IL‐1β and then attenuated CSE‐induced inflammation in HBE cells 117 . The expression level of miR‐181a‐5p was lower in the lung tissues of COPD model mice.…”
Section: Inhibition or Blockade Of Hmgb1 Rage And Tlr4 As A Potential...mentioning
confidence: 88%
“…This downregulated the release of TNF-α and IL-1β and then attenuated CSEinduced inflammation in HBE cells. 117 The expression level of miR-181a-5p was lower in the lung tissues of COPD model mice. However, miR-181a-5p overexpression targets HMGB1 to inhibit the NF-κB pathway, thus alleviating the inflammatory response in COPD mice.…”
Section: Effects Of Hmgb1 Inhibition Against Copd Inflammationmentioning
confidence: 94%
“…Several studies have reported the changes in miRNA expression in lung tissues obtained from COPD patients and animal models of COPD exposed to cigarette smoke 11 , 12 , 29 . Previous studies have demonstrated that miR-21 30 , miR-126 31 and miR-34a 28 play an important role in the pathogenesis and development of COPD. Our research group conducted microarray analysis of the lung tissues of CS and CSE exposure-induced emphysema mice and control mice and found that a few miRNAs were differentially expressed in the lung tissues of emphysema mice.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, CSE was diluted to the concentration of 40% for intraperitoneal injection into mice. The injection details were established as reported previously 23 . The mice in the control group were given 0.3 mL/20 g PBS through intraperitoneal injection, and the mice in the CS exposure group were given 0.3 mL/20 g, 40% CSE through intraperitoneal injection on days 1, 12, and 23.…”
Section: Cs Exposure Plus Cse-induced Mouse Modelmentioning
confidence: 99%